Measuring the Level of Voluntary Disclosure of Information in the Published Annual Financial Reports of Iraqi Banks: An Applied Study on a Sample of Banks Listed in the Iraq Stock Exchange - Yasamin Akram Saleem; Nissrat Saber Sheikha; Adnan Nader Hammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The accounting profession has witnessed a qualitative transformation in the last three decades in light of scientific and technical developments, So that it has become an integrated and comprehensive information system that serves all activities and businesses in various sectors, This is where the accounting disclosure has become an essential and effective means in the media and reporting of the outputs of the accounting system and their delivery to all users in the administration, investors and stakeholders, In a way that enhances their ability to make appropriate decisions, to the qualitative transformation that has occurred in the accounting profession, In exchange for the mandatory disclosure concerned with providing the minimum amount of accounting information as determined by the legal frameworks and professional standards, The voluntary disclosure has emerged as a trend that some banks take to disclose the largest amount of information that goes beyond the limits of what they are obligated to do in order to serve the users of financial statements, This, in turn, drew the researchers' attention to conduct many studies and researches concerned with measuring the level of voluntary disclosure in banks. And its role in serving and achieving its strategic objectives, And its role in serving and achieving its strategic objectives, and the problem of the current research is to measure the level of voluntary disclosure of information in the published annual financial reports of Iraqi banks listed on the Iraq Stock Exchange, This is done by developing a tool to measure the level of voluntary disclosure of information in the published annual financial reports In addition, the results of the study showed that the voluntary disclosure of public information about banks comes in first place with a rate of (84.6%). This is followed by management discussions and analysis of business data (83.8%), And then internal control and audits (81.9%). The study recommended the necessity of continuing to raise the level of voluntary disclosure in Iraqi banks, The necessity of increasing attention to the optional disclosure by the Iraqi Securities Commission and the scientific, professional and academic organizations and societies, This is to ensure that users of financial reports have access to additional financial and non-financial information, which helps them to make rational investment decisions.